Economic impacts of oral diseases in 2019: data for 194 countries - Jevdjevic, Milica; Listl, Stefan (Universität, 2022)
Data for the global, regional, and country-level economic impacts of oral diseases in 2019. Methodology is based on: (1) Listl S, Galloway J, Mosse...